Occurrence of Marbled Balloon Frog, Uperodon Systoma (Schneider, 1799) from Aurangabad (M.S.), India - Hiware, Sujeet Jamdar*, Tushar Dhondge and C.J. (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">During the survey of amphibians from University campus of Aurangabad (M.S.), India two specimens of marbled balloon frog were recovered near the botanical garden. Biodiversity study of amphibians from the university campus was not carried out before this study thus it forms the first study of amphibians and also occurrence of the marbled balloon frog from Marathwada region. The study was carried out during the year June 2009. The morpohmetric characters of this frog is taken into consideration while studying. <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">--- Department of Zoology, Dr.Babasaheb Ambedkar Marathwada University, Aurangabad (M.S.), India --- Please Cite This Article As: Sujeet Jamdar, Tushar Dhondge and C.J. Hiware. 2010. Occurrence of Marbled Balloon Frog, Uperodon Systoma (Schneider, 1799) from Aurangabad (M.S.), India. J. Ecobiotechnol. 2(6):4-6.